Pola Pengembangan Sebab-Akibat Dalam Paragraf Eksposisi Pada Siswa Kelas X Semester Genap SMA Negeri 14 Bandar Lampung - Frieska Maryova Rachmasisca; Surastina Surastina; Refki Refki (LPPM STKIP PGRI Bandar Lampung, 2023)
This study discusses students' ability to develop exposition paragraphs using a causal development pattern. The ability to develop exposition paragraphs with a pattern of cause-and-effect development is one way to develop ideas into main ideas and then into paragraphs that are complete and full of information that is in accordance with facts. The purpose of this study is to find out and describe the level of students' abilities in developing exposition paragraphs with a causal pattern. The method used to achieve the objectives of this research is to use a quantitative descriptive method. The data collection technique in this study used the performance test technique, namely assigning students to develop paragraphs with a causal pattern to become exposition paragraphs. The sample in this study was class X students in the even semester of SMA Negeri 14 Bandar Lampung, totaling 25 students. The level of ability to develop exposition paragraphs with a causal pattern for students is in the sufficient category with an average score of 61. The level of student ability based on the aspects assessed are: (1) the overall organization of paragraphs with a value of 66 is included in the sufficient category, (2) ) paragraph unity with a value of 65 is included in the sufficient category, (3) paragraph cohesiveness with a value of 47 is included in the less category, (4) paragraph development with a value of 66 is included in the sufficient category, (5) writing and neatness with a value of 65 is included in the sufficient category .